The usage effect of nano-alumina on the mechanical and surface properties of HDF made of oxidized fibers - Saeb Shabanpour (Regional Information Center for Science and Technology (RICeST), 2018)
Current research was conducted to investigate the effect of nano Alumina modification on the mechanical and Surface properties of High-Density Fiberboard (HDF) made from oxidized fibers. Surface activation of fiber was done with 40% nitric acid. After fibers gluing with urea-formaldehyde (7% and 9% based on the dry weight of fibers), the boards were made by hot pressing. For veneering, two types of paper with grammage of 70 and 80 g/m2 impregnated with melamine-formaldehyde and nano-alumina 0, 1.5 and 3% were applied. According to the results, the highest bending strength, modulus of elasticity and hardness were measured in nitric acid-modified fibers/ 9% glue/ grammage of 80 g/m2/3% nano-alumina samples that was significant increase compared to the control boards a significant increase. The samples weight loss due to abrasion was decreased with increasing the veneers grammage and nano-alumina, which confirmed the positive effect of nano-alumina. Veneer grammage did not show significant effect on the resistance to cigarette burn, but the highest concentration of nano-alumina resulted to improve this surface resistance via increase of thermal conductivity.